Impact of Entrepreneurship Course on Entrepreneurial Intention among Undergraduate Students of Al-Hikmah University, Kwara State, Nigeria - Jimoh Abdulrasheed; Yusuf Suleiman; Bolaji Hameed Olalekan (UII, 2019)
Unemployment has become one of the most newsworthy concerns in Nigeria. It has reached a level in which graduates of higher institutions have to normally wait for a long time before getting a job. Hence, the importance of entrepreneurship in terms of job creation and economic growth cannot be overemphasized. This research therefore examined the impact of entrepreneurship course on entrepreneurial intention among undergraduate students of Al-Hikmah University, Kwara State, Nigeria. The population of the study consists of 2800 while quota, simple random and convenience sampling techniques were used to 338 students from seven faculties. Instrument titled “Entrepreneurship Course and Entrepreneurial Intention Questionnaire (ECEIQ)” was used to elicit data from the respondents while Statistical Package for Social Sciences (SPSS) was used to analyse the data. Findings revealed that the teaching of entrepreneurship course significantly impact on student's knowledge and their entrepreneurial intention to start-up business. Findings also indicate perceived challenge which include poor state of infrastructure (electricity, road etc.) and lack of fund dampen students’ spirit of becoming an entrepreneur. Also, availability of infrastructure and fund are students’ perceived solutions to the challenges of becoming an entrepreneur. In view of the findings, this study therefore recommends that university should device a strategy to assist the students that indicate intention to start enterprise while in school and after graduation. Lastly, stakeholders in education should assist the university in providing equipment and funds for the advancement of entrepreneurship.